Pengaruh Gaya Kepemimpinan, Kepuasan kerja dan komitmen organisasi terhadap kirenja guru. - Endah Yanuarti (MM 14 UMY 019, 2014)
For every organization, evaluation toward work performance is important to find out how well the goal of an organization has been achieved in certain period. The information on work performance will be useful to evaluate not only the performance of an organization, whether its goals have been achieved or not, but also the process to achieve it, whether it needs improvement or not. Meaning, evaluation towards work performance can be used as the standard of success of an organization and also meaningful input in improving the work performance of an organization in the future. This research aims to analyze the influence ofleadership style, job satisfaction and organizational comitment gainst the teacher performance of the SMK Muhammadiyah Gunungkidul employees. Obyect research of SMK Muhammadiyah 1 Wonosari, SMK Muhammadiyah 1 Patuk dan SMK Muhammadiyah 1 Tepus Gunungkidul employees, respondents in this research are 121 teachers. The data gathering methods used by the writer are questionnaire methods. The result of analysis, leadership style, job satisfaction and organizational comitmen gives the influence positive and significantto teacher performance. The dominant variabels which influences the work performance is comitment organization. Keywords : Teacher performance, Leadership style, Job satisfaction, Organizational comitment.